The Big Boom Theory: The Common Nighthawk wing-boom display delineates exclusive nesting territories. Issue 1 (22nd October 2021) - Knight, Elly C; Brigham, R Mark; Bayne, Erin M
Abstract: Understanding the functional significance of bird sounds can provide valuable insight into the behavior and how birds use habitat. We show that the Common Nighthawk ( Chordeiles minor ) wing-boom display is a territorial signal associated with the nest location that can be used to identify territorial habitat use. In other words, the Common Nighthawk wing-boom display can be considered analogous to song due to its potential function in territoriality. We captured, tagged, and tracked 21 male Common Nighthawks in northeastern Alberta to confirm the functional significance of the wing-boom display and describe Common Nighthawk territoriality. Mean wing-boom use density (hereafter "area") size was 10.2 ha (SD = 11.7 ha). We found minimal overlap in the wing-boom area (5 of 15 neighboring male pairs, 0.2–4.5% overlap), suggesting the wing-boom display represents an exclusive territory. Comparison of wing-boom locations and random points within the wing-boom area confirmed that male Common Nighthawks select areas near the nest to perform wing-boom displays. There was high wing-boom area overlap for the same individual between years. Differences between years reflected shifts in nest location, suggesting that the wing-boom display is a good indicator of the nest location and territory. Future Common Nighthawk surveys should record the type of acoustic signal observed to differentiate territorial habitat use from other functions. Many taxa that produce non-vocal sounds as part of breeding displays could similarly benefit from a functional understanding to provide insight into habitat use. Graphical Abstract: Lay Summary: Understanding the functional significance of bird sounds is important because it provides behavioral context to detections. We tracked individual adult male Common Nighthawks and confirmed that the aerial wing-boom display represents an exclusive territory. Individual nighthawks selected areas near the nest location to perform wing-boom displays. Individuals had high territory overlap between years, with differences reflecting shifts in nest location. Future Common Nighthawk surveys should record the type of acoustic signal observed to differentiate territorial habitat use.